1989
DOI: 10.1155/tsm.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cube Texture in Coarse Grained Copper

Abstract: Cube oriented deformed material has been detected in the rolling texture measured on edge sections of heavily rolled coarse grained copper. The level of intensity is low, and seems to be independent of rolling reduction over the range 93–98%. Recrystallization textures show an increasing strength of Cube with rolling reduction. The evidence is consistent with the idea that Cube nuclei are created by a mechanism similar to that proposed by Dillamore and Katoh, and the strength of the recrystallized Cube texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…In the present case, the effect of starting grain size is quite pronounced at low annealing temperatures, and although this diminishes at higher annealing temperatures, the effect is still quite evident. These results amply corroborate and extend the generally accepted observation of the detrimental effect of coarse starting grain size on the development of cube texture [10,13] to ultrahigh deformation regime.…”
Section: A Deformed and Annealed Conditionsupporting
confidence: 88%
“…In the present case, the effect of starting grain size is quite pronounced at low annealing temperatures, and although this diminishes at higher annealing temperatures, the effect is still quite evident. These results amply corroborate and extend the generally accepted observation of the detrimental effect of coarse starting grain size on the development of cube texture [10,13] to ultrahigh deformation regime.…”
Section: A Deformed and Annealed Conditionsupporting
confidence: 88%
“…Similarly, Juul Jensen et al (1988) obtained much weaker textures with more random orientations in coarse grained AI-FeSi (99.5%) after complete recrystallization. Furthermore, the results coincide with experimental f'mdings by Sindel et al (1990) and Duggan and Chung (1994), who reported that in pure Cu the intensity of the Cuberecrystallization texture was substantially enlarged when the initial grain size was smaller. With increasing degree of deformation the Cube-orientation decreases as well ( Figure 6).…”
Section: Recrystallized Samplessupporting
confidence: 88%
“…Consequently, the increase of B at the expense of C is much less pronounced in the originally fine grained sample "F" (Figure 2a). A retardation of the rolling texture development in coarse grained material has already been described by Juul Jensen et al (1986), Leffers et al (1987) and Sindel et al (1990). It can be explained by differences in the flow pattern: In coarse grained samples generally a higher level of deformation heterogeneities exists, as e.g.…”
Section: Recrystallized Samplesmentioning
confidence: 70%
“…On the other hand, the 〈221〉 directions are deviated from 〈331〉 directions shown in the IPFs by an angle of ≈6.3˚. In [11], the authors performed a thorough analysis of twin maxima in direct experimental pole figures in a coarse-grained rolled copper with grain sizes of 50 and 500 μm and in a fully annealed copper. The analysis has shown that the exact location of the twin maxima in the pole figures deviates from the ideal positions of {122}〈212〉 twins by 2˚ -3˚ to 9˚, depending on the degree of preliminary rolling.…”
Section: The Initial Texture and Microstructurementioning
confidence: 99%
“…After bending on 1/2 part of cycle on the one side of stainless steel sample is formed component B of shear texture. There are also orientations of twinning, which form the orientations of texture {110}〈112〉 and {110}〈001〉 in metals and alloys with low SFE [11,12]. In the sample after 1 cycle of alternating bending is formed component C of shear texture.…”
Section: Effect Of Stacking Fault Energymentioning
confidence: 99%